Dendritic Spine and Synaptic Plasticity in Alzheimer’s Disease: A Focus on MicroRNA - Reza-Zaldivar, Edwin Estefan; Hernández-Sápiens, Mercedes Azucena; Minjarez, Benito; Gómez-Pinedo, Ulises; Sánchez-González, Victor Javier; Márquez-Aguirre, Ana Laura; Canales-Aguirre, Alejandro Arturo (Frontiers in Cell and Developmental Biology, 2020)
Dendrites and dendritic spines are dynamic structures with pivotal roles in brain connectivity and have been recognized as the locus of long-term synaptic plasticity related to cognitive processes such as learning and memory. In neurodegenerative diseases, the spine dynamic morphology alteration, such as shape and spine density, affects functional characteristics leading to synaptic dysfunction and cognitive impairment. Recent evidence implicates dendritic spine dysfunction as a critical feature in the pathogenesis of dementia, particularly Alzheimer’s disease. The alteration of spine morphology and their loss is correlated with the cognitive decline in Alzheimer’s disease patients even in the absence of neuronal loss, however, the underlying mechanisms are poorly understood. Currently, the microRNAs have emerged as essential regulators of synaptic plasticity. The changes in neuronal microRNA expression that contribute to the modification of synaptic function through the modulation of dendritic spine morphology or by regulating the local protein translation to synaptic transmission are determinant for synapse formation and synaptic plasticity. Focusing on microRNA and its targets may provide insight into new therapeutic opportunities. In this review we summarize the experimental evidence of the role that the microRNA plays in dendritic spine remodeling and synaptic plasticity and its potential therapeutic approach in Alzheimer’s disease. Targeting synaptic deficits through the structural alteration of dendritic spines could form part of therapeutic strategies to improve synaptic plasticity and to ameliorate cognitive impairments in Alzheimer’s disease and other neurological diseases.